Android-Based Mathematics Learning Media Assisted by Smart Apps Creator on Self-Regulated Learning - Isnaini Mahuda; Anton Nasrullah; Melinda Putri Mubarika; Ranny Meilisa; Laksmi Evasufi Widi Fajari (International Journal of Asian Education, 2022)
This study aimed; 1) to investigate student responses toward the use of android-based media assisted by Smart Apps Creator for mathematics learning; 2) to investigate student self-regulated learning level; 3) to find out whether there was an effect using Android-based mathematics learning media assisted by Smart Apps Creator on student self-regulated learning. The study used an experimental method One-Shot Case research design. This study took the population of second-semester students in the Department of Management. The research samples were 2B MAN students chosen by random cluster sampling. The study showed that the percentage of average student responses to Android-based learning media assisted by Smart Apps Creator was very high, 88.08% and students' self-regulated learning was in a high category at 75.87%. The hypothesis test results indicated an effect of using Android-based mathematics learning media assisted by Smart Apps Creator on student self-regulated learning. The number of using android-based mathematics learning media on student self-regulated learning was 18.2%, the rest by other variables in this study. The researchers found the result of their research and concluded: 1) the average of student responses to the use of Android-based learning media assisted by Smart Apps Creator was 88.08% which is categorized powerful ad category; 2) the average of students’ self-regulated learning was 75.87% described as a strong category; 3) The results of hypothesis test showed there was an effect of using Android-based Mathematics learning media assisted by Smart Apps Creator on student self-regulated learning.